The formation of charismatic leadership among university students: an empirical analysis based on the determinants of physical, emotional, spiritual and intellectual - Mohamed, Hasan Al-Banna; Mohamad, Mohd Hamran; Ab Ghani, Sayuti; Baker, Rogis; Mohamed, Rosmah; Mohd Saudi, Nur Surayya (UPNM Press, 2021)
Leadership is a key pillar of the successful 21st century organizations and it is very crucial to ensure that its governance is always of the highest standard and remain relevant. Leadership without integrity is a risk to an organization and will disrupts the organization’s efficiency and effectiveness. Therefore, the process of developing a good leader is vital for university students who will be future leaders with a holistic and balanced spiritual and physical aspect of their life. This study was conducted to analyze the four concepts of P.E.S.I. namely Physical, Emotional, Spiritual and Intellectual that influence the preservation of leadership among students in a Malaysian institution of higher learning. The quantitative method was used in this study where self-administered questionnaires were employed as a research instrument. The sample (n=342) was collected from students of a public university in Malaysia. The results found that there were significant relationships between the four concepts of P.E.S.I. and the formation of charismatic leadership among students of a public university in Malaysia. This study is expected to be an important source of reference for public universities in Malaysia to develop exemplary leaders.